Pyralis transcaspica Rebel, 1903 (Lepidoptera: Pyralidae), a little-known species newly recorded from Kyrgyzstan, Kazakhstan and Tajikistan - Huemer, Peter; Korb, Stanislav (Zootaxa, 2026)
Pyralis transcaspica Rebel, 1903 is redescribed, key identification features are listed, and imago and male genitalia are figured. This species is firstly recorded from Kyrgyzstan, Kazakhstan and Tajikistan. Habitats of P. transcaspica Rebel, 1903 are described and figured. Pyralis transcaspica Rebel, 1903 and P. perversalis (Herrich-Schäffer, 1849) are compared by their morphology and COI sequence; both features confirmed species delimitation.